Factors Driving Consumer Restaurant Choice: An Exploratory Study from the Southeastern United States - Alonso, Abel; O'neill, Martin; Liu, Yi; O'shea, Michelle (Routledge, 2013)
This study investigates the critical dimension of factors driving restaurant choice among 277 consumers, predominantly residents of the Southeastern United States. The food provided (quality, taste) was central to respondents’ decision to favor one restaurant over another, though prior positive experience, a clean production/service environment and hospitable service are additional factors that most strongly influenced restaurant choice. Interestingly, despite the rich variety of foods/produce and agricultural background of the region, the use of local food and produce in menu development is among the least considered factors. Several implications are drawn from the findings and directions for future studies are suggested.